Food taboos for pregnant women in Bajo Tribe in Petoaha, Kendari City - Lestari, Hariati; Muchtar, Febriana (Universitas Islam Negeri Alauddin Makassar, 2024)
Food taboo is a habit of abstaining from food that is carried out for generations, especially for pregnant women, which is not necessarily true so that it can cause a lack of nutritional intake during pregnancy. The purpose of this study was to determine the description of knowledge and cultural taboos for pregnant women in the Bajo tribe in Petoaha Village, Kendari City. The method used in this study is descriptive quantitative using a Cross Sectional study design and was conducted in October 2022 in Petoaha Village, Abeli District, Kendari City. The sample used was 265 people. The sampling technique in this study used simple random sampling. The results showed that there were several foods that were considered taboo for pregnant women in the Bajo tribe including: pineapple, jackfruit, durian, chili, shrimp, clams, squid, octopus, stingray, skipjack, catfish, turtle eggs and crabs on the grounds that they could harm pregnant women and their fetuses. Conclusion: there are several foods that are considered taboo for pregnant women in the Bajo tribe. Suggestion: education is needed for the Bajo tribe, especially pregnant women, regarding the importance of nutritious food consumption, particularly during pregnancy.